The motivation to use the network of information resources among the students of Al-Mustansiriya University (Journal of the College of Basic Education, 2023)
The electronic information network, as one of the most prominent technologies in the field of the international information network in the world, has made a strong impact on the volume of information provided to people at a lower cost, shorter time, and greater achievement. The electronic information network for higher education provides many benefits and great research services, through which the student can enter international libraries and see the intellectual results of scientists and researchers while he is at his university. It is a huge warehouse that contains books, scientific papers, data, lectures and audio recordings.In addition to that, developing programs that help increase information awareness among students, evaluating students' behavior in using the electronic information network, and knowing the motives that drive them to this behavior is very important because treatment, whether developmental, preventive, or therapeutic, does not happen except by knowing the motives behind this behavior, so there is no behavior Without motives. So the problem is determined by identifying:1 - Motivation to use the network of information resources among university students 02 - Motivation to use the network of information resources among university students according to the variable of gender (male - female) and specialization (scientific - human).The current research is represented by the students of Al-Mustansiriya University, College of Education, for the academic year (2010-2011) for the two departments (computers and psychological counseling).After applying the tool and using appropriate statistical methods in the light of the objectives of the current research, the following results were reached:1- The motivation of the research sample is weak towards using the network of information resources2- There is a slight difference between males and females and in favor of females in the motivation to use the network of information resources.3- There is a difference in motivation according to the variable of specialization and in favor of the humanitarian departments towards using the network of information resources.In light of these results, the researchers put forward a number of recommendations and proposals